Constitutive heterochromatin, G-bands and nucleolus-organizer regions in four species of Didelphidae (Marsupialia) - Yononaga-Yassuda, Y.; Kasahara, S. [UNESP]; Souza, M. J.; L'Abbate, M. (Springer Nature, 1982)
Chromosomes of Didelphis albiventris, D. marsupialis, Philander opossum and Lutreolina crassicaudata, four species of marsupials with very similar karyotypes and 2n=22 were studied. All the chromosomes were acrocentrics except the X in L. crassicaudata, which is a metacentric. The G-band patterns of these species are similar but the distribution of constitutive heterochromatin differs among them as shown by C-banding. The hypothesis that the X in L. crassicaudata might be an isochromosome derived from the acrocentric X in the other species is discarded since G-and C-banding patterns differ in the two arms. In D. marsupialis the Ag-NORs are terminal and located in both arms of one pair and in the long arms of two pairs of medium-sized autosomes. In P. opossum the NOR-bearing chromosomes could be precisely identified through simultaneous silver staining and G-banding. The Ag-NORs are terminal and located at the short arm of pair 5 and the long arm of pair 7. © 1982 Dr W. Junk Publishers.